Modeling of glutamic acid production by Lactobacillus plantarum MNZ - Zareian, Mohsen; Ebrahimpour, Afshin; Sabo Mohammed, Abdul Karim; Saari, Nazamid (Electronic Journal of Biotechnology, 2013)
Background: L-glutamic acid, the principal excitatory neurotransmitter in the brain and an important intermediate in metabolism acts as a precursor of γ-amino butyric acid (GABA). In the present study, culture condition for enhanced glutamic acid production by Lactobacillus plantarum MNZ was optimized and the influence of such conditions on GABA production was evaluated. Results: Results indicated that glutamic acid increased up to 3-fold (3.35) under the following condition: pH 4.5, temperature 37ºC, 12% (w/v) glucose and 0.7% (w/v) ammonium nitrate; whilst GABA production was enhanced up to 10-fold under the following condition: pH 4.5, temperature 37ºC, 6% (w/v) glucose and 0.7% (w/v) ammonium nitrate. Conclusions: This is the first report for dual biosynthesizing activities of a lactic acid bacterium for the production of glutamic acid and GABA. The results of this study can be further used for developing functional foods rich inglutamic acid and subsequently GABA as a bioactive compound.